Portal hypertension in primary biliary cirrhosis. Issue 10 (October 1971) - Kew, M. C.; Varma, R. R.; Santos, H. A. Dos; Scheuer, P. J.
Abstract : Evidence of portal hypertension was found in 50 out of 109 patients (47%) with primary biliary cirrhosis, and of these 32 bled from oesophageal varices. In four patients portal hypertension was the initial manifestation of the disease and this complication was recognized in a further 17 within two years of the first symptom of primary biliary cirrhosis. The development of portal hypertension was associated with a poor prognosis and death could frequently be attributed to variceal bleeding; the mean duration of survival from the time that portal hypertension was recognized was 14·9 months. Portal decompression operations may have improved the immediate prognosis in some patients but did not otherwise influence the progression of the disease. In 47 patients the histological findings in wedge biopsy or necropsy material were correlated with the presence or absence of varices. An association between nodular regeneration of the liver and varices was confirmed, but, in the absence of nodules, no other histological cause for portal venous obstruction could be found.